PENGARUH PEMANFAATAN SISTEM PENGADAAN, KOMPETENSI SDM DAN TINGKAT KEMATANGAN ORGANISASI TERHADAP KINERJA PEGAWAI BAGIAN PENGADAAN BARANG/JASA KABUPATEN PASURUAN - Rakhmawati, Rusita; Sundjoto; Sri Rahayu (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to analyze the influence of procurement system utilization, human resource (HR) competence, and organizational maturity level on the performance of employees in the Procurement of Goods/Services Division of Pasuruan Regency. The population consists of all 50 employees in the division, and the research uses a census method. The data analysis technique applied is multiple linear regression. The results show that: (1) Procurement system utilization has a positive impact on employee performance by enhancing efficiency, transparency, and accountability in task execution; (2) HR competence significantly contributes to performance improvement, as employees with adequate knowledge, skills, and work attitudes tend to be more productive; (3) The level of organizational maturity positively influences employee performance by creating a systematic and supportive work environment; and (4) Simultaneously, the three variables collectively have a significant positive impact on employee performance. These findings highlight the importance of system integration, competency development, and organizational maturity in enhancing work effectiveness in the public procurement sector.